Safety and efficacy of transurethral laser lithotripsy and percutaneous laser lithotripsy in 41 dogs with lower urinary tract stones - Shigemoto, Jin; Kawazu, Mitsunobu (Frontiers in Veterinary Science, 2025)
ObjectiveThe clinical application of transurethral laser lithotripsy (TUL) for lower urinary tract stone removal in dogs is constrained by factors such as body weight, stone size, and stone number. This study evaluated the safety and efficacy of TUL and percutaneous laser lithotripsy (PL) in cases where TUL alone was not feasible.Study designRetrospective study.Animal populationForty-one dogs (24 males, 17 females) were included between June 15, 2017, and January 26, 2023. Among them, 13 males were castrated and 14 females spayed.MethodTUL was performed using a holmium:yttrium-aluminum-garnet (Ho:YAG) laser, an 8.5Fr flexible ureteroscope, and a 9.5Fr rigid cystoscope for urethral and bladder stone fragmentation. PL was conducted using a Ho:YAG laser in combination with percutaneous cystolithotomy (PCCL).ResultsTUL was performed in 34 dogs, including 22 males (64.7%) and 12 females (35.2%). Laser lithotripsy was categorized by endoscope type and stone location. Of these, 33 dogs (94.1%) completed the procedure, while one male (2.9%) required conversion due to excessive bleeding. PL was performed in seven dogs (two males, 28.5%; five females, 71.4%), all of whom (100%) completed the procedure without conversion. Complications from laser lithotripsy occurred in five males (12.1%) of 41 dogs.ConclusionTUL is a minimally invasive urethral procedure, but its feasibility is limited in underweight dogs where endoscope insertion is impractical.Clinical significanceWhen TUL alone is unviable, combining it with PL provides a safe and effective laser lithotripsy approach for bladder and urethral stones, regardless of the dog's weight or sex.